2013
DOI: 10.1186/1472-6955-12-17
|View full text |Cite
|
Sign up to set email alerts
|

The challenges of communicating research evidence in practice: perspectives from UK health visitors and practice nurses

Abstract: BackgroundHealth practitioners play a pivotal role in providing patients with up-to-date evidence and health information. Evidence-based practice and patient-centred care are transforming the delivery of healthcare in the UK. Health practitioners are increasingly balancing the need to provide evidence-based information against that of facilitating patient choice, which may not always concur with the evidence base. There is limited research exploring how health practitioners working in the UK, and particularly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
(44 reference statements)
1
6
0
Order By: Relevance
“…This resulted in parents perceiving that many HCPs lacked flexibility in the scope of information and advice they could, or would, offer. Therefore, similar to previous studies, results of the current study suggest that HCPs face challenges in delivering evidence‐based information to parents in everyday practice (van Bekkum & Hilton, ).…”
Section: Discussionsupporting
confidence: 87%
“…This resulted in parents perceiving that many HCPs lacked flexibility in the scope of information and advice they could, or would, offer. Therefore, similar to previous studies, results of the current study suggest that HCPs face challenges in delivering evidence‐based information to parents in everyday practice (van Bekkum & Hilton, ).…”
Section: Discussionsupporting
confidence: 87%
“…Of these studies, eight were conducted in the UK, two in New Zealand, one in Australia, and one in the Republic of Ireland (Table , Supporting Information Table S2). In every study, practice nurses were either identified as the sole participant group (Desmond, Grant, Goodyear‐Smith, Turner, & Petousis‐Harris, ; Lamden & Gemmell, ; Petousis‐Harris, Goodyear‐Smith, Turner, & Soe, ) or a discrete group in the sample (BMRB Social Research, ; Cotter, Ryan, Hegarty, McCabe, & Keane, ; Kennedy et al., ; Leask et al., ; Macdonald et al., ; Smith, McCann, & McKinlay, ; van Bekkum & Hilton, , ). Four themes addressing the question guiding this integrative review were identified, which were parental immunization influencing factors; practice nurse characteristics; information and communication, and personal views and concerns (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Practice nurses reported using different sources of information to inform their consultations, as identified in over half of the included papers (BMRB Social Research, ; Cotter et al., ; Leask et al., ; Macdonald et al., ; Petrovic et al., ; van Bekkum & Hilton, , ). Different sources of information accessed included the media; TV; the immunization co‐ordinator; the Department of Health website; the Green Book (This is an online publication that has the latest immunization information for vaccine preventable diseases in the UK), and Chief Medical Officers’ letters or updates on immunization (BMRB Social Research, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a survey of British nurses who regularly communicate scientific evidence to patients, nurses reported feeling less confident in their ability to convey information when patients challenged the evidence. The researchers concluded that a collaborative plan that integrates a woman's personal experience into the plan for screening may improve acceptance of evidence‐based guidelines (van Bekkum & Hilton, ). Based on their suggestions, I developed the four Cs framework to facilitate difficult discussions when evidence‐based practice is challenged (see Box ).…”
Section: An Approach Based On the Four Csmentioning
confidence: 99%